2020
DOI: 10.1111/jonm.12926
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological capital and innovation behaviour in Chinese nurses

Abstract: Aim:To explore the serial-multiple mediation of job control and perceived organisational innovation climate between psychological capital and innovation behaviour among Chinese nurses through structural equation modelling.Background: Nurses' innovation not only promotes the development of the nursing industry but also improves the quality of care and promotes patient prognosis. Thus, it is essential to clarify the factors affecting nurses' innovative behaviour and to provide a theoretical basis for improving n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
69
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 30 publications
9
69
2
Order By: Relevance
“…In addition, Ziyae et al [41] demonstrate a positive relationship between the dimensions of psychological capital (i.e., self-efficacy, hope, optimism, and resiliency) altogether and innovation in informational technology. Further, Yan et al [42] show a positive correlation between psychological capital (as a whole) and innovation behaviour in Chinese nurses. A recent article by Schuckert et al [43] found a positive relationship between psychological capital and innovative behaviour from full-time frontline employees of five-star hotels in Seoul, South Korea.…”
Section: Psychological Capital and Innovative Behaviourmentioning
confidence: 95%
“…In addition, Ziyae et al [41] demonstrate a positive relationship between the dimensions of psychological capital (i.e., self-efficacy, hope, optimism, and resiliency) altogether and innovation in informational technology. Further, Yan et al [42] show a positive correlation between psychological capital (as a whole) and innovation behaviour in Chinese nurses. A recent article by Schuckert et al [43] found a positive relationship between psychological capital and innovative behaviour from full-time frontline employees of five-star hotels in Seoul, South Korea.…”
Section: Psychological Capital and Innovative Behaviourmentioning
confidence: 95%
“…It is important to note that this limited research is detrimental because hospital employees are primary agents in implementing innovation at work [12,34]. Furthermore, numerous studies have focused on nurses [35], doctors [14], or medical students [36]. However, studying IIB from a partial perspective limits our general understanding of its role on all hospital employees [7].…”
Section: Individual Innovative Behaviormentioning
confidence: 99%
“…Although the factors shown in Figure 1 have previously been found to be related to innovative behavior [26,27,28], determinants (PsyCap, IMOC), and outcomes (OC), hospital employees' IIB has yet to be studied. Furthermore, numerous studies have focused on nurses, [29], doctors [14], or medical students [30] to explore the effects of IIB at work. However, studying IIB from a partial perspective limits our general understanding of its effects on all hospital employees [7].…”
Section: Individual Innovative Behavior (Iib)mentioning
confidence: 99%